Implementasi Undang-Undang Nomor 18 Tahun 2008 tentang Urgensi Pengadaan Tempat Sampah di Desa Tegalweru - Junaidi, Ahmad Khusnan (Maliki Interdisciplinary Journal, 2024)
This journal discusses the implementation of Law Number 18 of 2008 relating to the strategic importance of procuring waste bins in Tegalweru Village. This study aims to analyze the urgency and effectiveness of implementing the law in the context of waste management at the village level. The research methodology involves juridical and empirical approaches by means of field surveys, interviews, and data analysis to evaluate the extent to which the application of Law Number 18 of 2008 has achieved its objectives. The results showed that the implementation of the law has had a positive impact in increasing public awareness of waste management in Tegalweru Village. However, certain challenges such as limited resources and community participation are still obstacles in achieving waste management optimization. This study provides important insights for local governments and related institutions to continuously improve policies and strategies in an effort to achieve sustainable waste management goals at the village level.